Evaluation of Academic Success of Ankara University Faculty of Medicine Students According to the Social Determinants of Health - Filiz Ak Azar; Elif Nur Çakınberk; Melda Doğan; Yiğit Yahya İkizler; Ece Korkut; Ceyda Ceren Dönder; Sezin Naz Yıldırım; Cevdet Arda Selvi (Ankara Üniversitesi Tıp Fakültesi Mecmuas, 2025)
Objectives: The objective of this study is to investigate the association between social determinants of health (SDOH) and academic success among preclinical students at Ankara University Faculty of Medicine. We aim to provide insights for policies and practices that promote student well-being and ensure equitable support for academic achievement. Materials and Methods: A cross-sectional survey design was employed over a period of 18 months, from October 2021 to March 2023. Data was collected through an online survey using Google Forms, including demographic and academic achievement information, and analyzed using statistical tests. Ethical approval was obtained, and a sample of 153 participants was used for analysis. Results: This study was conducted with 153 preclinical students from Ankara University Faculty of Medicine and evaluated the SDOH. The participants, predominantly Turkish citizens (93.5%) and female (65.4%), had diverse accommodation arrangements, including living with parents (39.9%) or in a dormitory with roommates (32.0%). Factors such as access to healthcare, monthly income, safety, social support, and environmental conditions were assessed. Academic success, measured through a Likert scale, revealed that feeling non-discriminated and receiving psychological support significantly correlated with academic performance. However, other SDOH did not show a significant association with academic success. Conclusion: While SDOH other than feeling non-discriminated and receiving psychological support did not show significant correlations in our study, further research is needed to explore their impact. Creating a supportive and non-discriminatory environment is essential for the academic success and well-being of medical students.